Pengaruh Penggunaan Aspal Plastik Recycle dan Aspal Pen 60/70 Pada Campuran Aspal Panas AC-WC (Asphalt Concrete Wearing Course) Menggunakan Agregat Lokal Madura Terhadap Karateristik Marshall - asmaroni; Ahmad Fatoni; Alfita Yusriyah (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2023)
Roads are the basic and main infrastructure in driving the wheels of the national and regional economy. So it is necessary to plan a pavement structure that is strong and durable, for tropical areas such as Indonesia the type of asphalt that is often used is the type of asphalt pen 60/70 where the melting point ranges from 48-58. The existence of plastic is increasingly abundant, Indonesia is the second country that discharges plastic waste into the sea with an amount of approximately 1.3 tons per year. Therefore, the use of plastic waste in hot asphalt mixtures can be used as an alternative to reduce dependence on oil asphalt. In addition to the use of plastic waste in the hot asphalt mixture, another alternative that can be used is the use of local pamekasan aggregates as a constituent of the hot asphalt mixture. Therefore plastic asphalt is used as a mixture of asphalt and the use of asphalt pen 60/70 as a comparison using local Pamekasan aggregates. There are 27 test objects that will be made and will be tested to determine the Marshall characteristic value with reference to the requirements in the 2018 Highways Technical Specifications revision 2. From the test results, almost all mixtures using plastic asphalt can meet the requirements for Marshall characteristics. However, from all these types of mixtures it can be concluded that the optimum mixture is the use of Asphalt 4.9% with the highest Stability value of 1166 Kg with a VIM value of 3.98%, VMA 15.51%, VFB 74.33%, MQ 402kg/mm ​​and density value of 2.263 gr/cc.